2022
DOI: 10.3390/toxins14100669
|View full text |Cite
|
Sign up to set email alerts
|

sPLA2 Wobbles on the Lipid Bilayer between Three Positions, Each Involved in the Hydrolysis Process

Abstract: Secreted phospholipases A2 (sPLA2s) are peripheral membrane enzymes that hydrolyze phospholipids in the sn-2 position. The action of sPLA2 is associated with the work of two active sites. One, the interface binding site (IBS), is needed to bind the enzyme to the membrane surface. The other one, the catalytic site, is needed to hydrolyze the substrate. The interplay between sites, how the substrate protrudes to, and how the hydrolysis products release from, the catalytic site remains in the focus of investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In this case the catalytic site remains out of contact with the lipid bilayer, and thus the substrate cannot be bound. The possibility is based on the recent finding of multiple membrane-binding sites on the surface of sPLA2, only one of which is associated with the hydrolysis process [ 19 ]. The third possibility to prevent hydrolysis is to prevent a substrate from binding to the enzyme, keeping the catalytic site unaltered ( Figure 1 , process 3).…”
Section: Directions To Attack Spla2 To Control Its Enzymatic Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…In this case the catalytic site remains out of contact with the lipid bilayer, and thus the substrate cannot be bound. The possibility is based on the recent finding of multiple membrane-binding sites on the surface of sPLA2, only one of which is associated with the hydrolysis process [ 19 ]. The third possibility to prevent hydrolysis is to prevent a substrate from binding to the enzyme, keeping the catalytic site unaltered ( Figure 1 , process 3).…”
Section: Directions To Attack Spla2 To Control Its Enzymatic Activitymentioning
confidence: 99%
“…Recently, Kuzmina and co-authors [ 19 ] had reported that the bvPLA2 enzyme has three different membrane-binding modes ( Figure 3 ). This finding was obtained independently in “wet” experiments using atomic force microscopy and in silico experiments using molecular dynamics simulations.…”
Section: Blocking the Enzyme In The Wrong Orientation On The Membrane...mentioning
confidence: 99%
See 3 more Smart Citations